Organizational applications of business intelligence management emerging trends - Herschel, Richard T. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book offers a deep look into the latest research, tools, implementations, frameworks, architectures, and case studies within the field of Business Intelligence Management"--Provided by publisher.